Qualitative Exploration of Nursing Students' Perceptions of the Implementation of Objective Structured Clinical Examination (OSCE) - Ramadhan, Sukma Cahya; Septianingrum, Yurike; Amanda Wardani, Anandita; Mukarromah, Lu'luul (Universitas Muhammadiyah Lamongan, 2024)
ABSTRACT Introduction: The current method of measuring the clinical competency ability of nursing students is not only through CBT-based exams. One of the methods used to evaluate students' clinical skills is Objective Structured Clinical Examination (OSCE). The purpose of this study is to explore student perception of implementation (OSCE) as a method of evaluating student skills. Methods: This study uses qualitative exploration studies with a phenomenological approach to explore into students' experiences with the OSCE. The population in this study is nursing students (2019–2020) at private University at Surabaya. A total of nine students participated in this study according to the established inclusion criteria. The data collection was conducted through in-depth interviews through Zoom with semi-structural interviews and recorded by the researchers according to the participant's consent. The study was conducted from January 14th to February 1st, 2024. Data were analyzed using the Colaizzi method to determine themes and sub-themes. Results: According to the results of the study, five themes related to student perceptions of the implementation of the OSCE covered the level of knowledge, stressors, implementation management, coping mechanisms, and advantages of OSCE methods. Conclusion: These findings are expected to serve as a basis for the strategy of implementing OSCE as a method of clinical evaluation, especially in the scope of the College of Nursing Sciences. Keywords: Perception, Students, Nursing, OSCE.